Altered effective connectivity in the emotional network induced by immersive virtual reality rehabilitation for post-stroke depression - Wu, Jia-Jia; Zheng, Mou-Xiong; Hua, Xu-Yun; Wei, Dong; Xue, Xin; Li, Yu-Lin; Xing, Xiang-Xin; Ma, Jie; Shan, Chun-Lei; Xu, Jian-Guang (Frontiers in Human Neuroscience, 2022)
Post-stroke depression (PSD) is a serious complication of stroke that significantly restricts rehabilitation. The use of immersive virtual reality for stroke survivors is promising. Herein, we investigated the effects of a novel immersive virtual reality training system on PSD and explored induced effective connectivity alterations in emotional networks using multivariate Granger causality analysis. Forty-four patients with PSD were equally allocated into an immersive-virtual reality group and a control group. In addition to their usual rehabilitation treatments, the participants in the immersive-virtual reality group participated in an immersive-virtual reality rehabilitation program, while the patients in the control group received 2D virtual reality rehabilitation training. The Hamilton Depression Rating Scale, modified Barthel Index, and resting-state functional magnetic resonance imaging (rsfMRI) data were collected before and after a 4-week intervention. rsfMRI data were analyzed using multivariate Granger causality analysis. We found that the immersive virtual reality training was more effective in improving depression in patients with PSD but had no statistically significant improvement in modified Barthel Index scores compared to the control group. The Granger causality analysis showed that the following causal connectivities were strengthened after immersive virtual reality training: from the amygdala, insula, middle temporal gyrus, and caudate nucleus to the dorsolateral prefrontal cortex; from the insula to the medial prefrontal cortex; and from the thalamus to the posterior superior temporal sulcus. These causal connectivities were weakened after treatment in the control group. Our results indicated the neurotherapeutic use of immersive virtual reality rehabilitation as an effective nonpharmacological intervention for PSD; the alteration of causal connectivity in emotional networks might constitute the neural mechanisms underlying immersive-virtual reality rehabilitation in PSD.